Electrochemical and in situ spectroelectrochemical properties of metal-free and metallophthalocyanines containing alpha-naphtholbenzein groups on the peripheral positions - ÖZKAYA, ALİ RIZA (SPRINGER, 2016)
Phthalocyanine (Pc) compounds-containing alpha-naphtholbenzein units have been synthesized and characterized by spectroscopic data and elemental analysis. The redox properties of the compounds were investigated by cyclic and square wave voltammetry, controlled-potential coulometry and in situ spectroelectrochemistry in DMSO and compared with the free phthalonitrile ligand. The Pc compounds displayed common metal and/or ring-based reduction and oxidation processes. However, electrochemical measurements clearly suggested that the substituents involving anthraquinone units are redox active and so have a considerable effect on the redox processes of these compounds.
Keywords: HETERO-DINUCLEAR PHTHALOCYANINES; BALL-TYPE PHTHALOCYANINES; GAS-SENSING PROPERTIES; MONO